2017
DOI: 10.1101/101170
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Muscle transcriptome analysis reveals molecular pathways and biomarkers involved in extreme ultimate pH and meat defect occurrence in chicken

Abstract: The processing ability and sensory quality of chicken breast meat are highly related to its ultimate pH (pHu), which is mainly determined by the amount of glycogen in the muscle at death. To unravel the molecular mechanisms underlying glycogen and meat pHu variations and to identify predictive biomarkers of these traits, a transcriptome profiling analysis was performed using an Agilent custom chicken 8×60K microarray. The breast muscle gene expression patterns were studied in two chicken lines experimentally s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 54 publications
(67 reference statements)
5
8
0
Order By: Relevance
“…These findings suggest that the higher tenderness detected in the L-histidine supplementation group was not caused by changes in the extracellular matrix (e.g., due to changes in collagen synthesis). Of the BP terms listed in Table 3, wound healing and gluconeogenesis were also identified among the top 10 enriched GO terms in a transcriptome study on the breast muscles of two broiler chicken lines that showed significant differences in meat quality (ultimate pH, muscle glycolytic potential, and toughness) [45]. In this study, we found that the L-histidine supplementation group showed downregulation of the 6-phosphofructo-2-kinase/fructose-2,6-biphosphatase 1 and phosphoglycerate mutase 1 (PGAM1) genes, upregulation of the cryptochrome circadian regulator 1 gene, and enrichment in the gluconeogenesis function.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that the higher tenderness detected in the L-histidine supplementation group was not caused by changes in the extracellular matrix (e.g., due to changes in collagen synthesis). Of the BP terms listed in Table 3, wound healing and gluconeogenesis were also identified among the top 10 enriched GO terms in a transcriptome study on the breast muscles of two broiler chicken lines that showed significant differences in meat quality (ultimate pH, muscle glycolytic potential, and toughness) [45]. In this study, we found that the L-histidine supplementation group showed downregulation of the 6-phosphofructo-2-kinase/fructose-2,6-biphosphatase 1 and phosphoglycerate mutase 1 (PGAM1) genes, upregulation of the cryptochrome circadian regulator 1 gene, and enrichment in the gluconeogenesis function.…”
Section: Discussionmentioning
confidence: 99%
“…The glucose-6-phosphate isomerase, fructose bisphosphate aldolase, phosphoglycerate kinase, and enolase were down-regulated and GAPDH, phosphoglycerate mutase, and pyruvate kinase were up-regulated in the 7 th -day embryo of improved Aseel. Fructose bisphosphate aldolase is a key enzyme in glycolysis as well as gluconeogenesis and involved in the stress-response pathway during hypoxia [148]. The high pH chickens have increased oxidative stress, maybe the higher expression of fructose bisphosphate aldolase is linked to its function in the stress-response pathway rather than to its role in ATP biosynthesis [149].…”
Section: Energy Sensingmentioning
confidence: 99%
“…high (pHu+) and low (pHu-) using an Agilent custom chicken 8×60K microarray. Between two lines, 1436 differentially expressed (DE) genes were found and they are related to biological processes for muscle development and remodeling, carbohydrate, and energy metabolism [9]. A genome-wide association study (GWAS) was conducted for assessing body weight in an F2 chicken population and a microarray expression study was done with the liver of high and low-weight chickens.…”
mentioning
confidence: 99%
“…The results of multiple studies show that the quality of poultry meat has recently decreased, which could be observed due to the appearance of defects such as: PSE-like, white stripping ( WS ), wooden breast ( WB ), Oregon disease, spaghetti meat defect ( SM ), or increased drip loss ( Nadaf et al, 2007 ; Kuttappan et al, 2017 ; Schilling et al, 2017 ; Zampiga et al, 2018 ). In order to explain such myopathies modern science, for instance genomics, proteomics, and metabolomics recently has been applied ( Beauclercq et al, 2017 ; Kuttappan et al, 2017 ; Boerboom et al, 2018 ; Zampiga et al, 2018 ; Pampouille et al, 2019 ). The genomic research concerning WB and WS myopathies showed many differences in expression level of genes related to numerous metabolic pathways and consequently indicated that the selection for increased feed efficiency and growth rate might have changed expression and molecular pathways in breast muscle, resulting in an increased incidence and severity of muscle abnormalities ( Zampiga et al, 2018 ; Pampouille et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%